Participation of CWINV and SUS Genes in Sucrose Utilization in the Disruption of Cambium Derivatives Differentiation of Silver Birch - Moshchenskaya, Yulia L.; Galibina, Natalia Alekseevna; Serkova, Aleksandra Aleksandrovna; Tarelkina, Tatyana Vladimirovna; Nikerova, Ksenia Michailovna; Korzhenevsky, Maksim Anatol'evich; Sofronova, Irina Nikolaevna; Semenova, Ludmila Igorevna (Protein and Peptide Letters, 2024)
Background: The mechanisms that control the accumulation of woody biomass are of great interest to the study. Invertase and sucrose synthase are enzymes that are vital for distributing carbon in various biosynthetic pathways. Karelian birch (Betula pendula var. carelica) is a form of silver birch (B. pendula Roth) and is characterized by disruption of the differentiation of cambium derivatives towards both the xylem and phloem, which leads to a change in the proportion of the conducting tissues' structural elements and the figured wood formation. We researched the expression profiles of genes encoding sucrose-cleaving enzymes (CWINV and SUS gene families) and genes encoding CVIF protein, which is responsible for the post-translational regulation of the cell wall invertase activity. Objective: In our study, 16-year-old common silver birch (Betula pendula var. pendula) and Karelian birch were used for sampling non-figured and figured trunk section tissues, respectively. Samples were selected for the research based on the radial vector: non-conductive, conductive phloem, cambial zone - differentiating xylem - mature xylem. Methods: The enzyme's activity was investigated by biochemical methods. RT-PCR method was used to determine the level of gene expression. Anatomical and morphological methods were used to determine the stage of differentiation of xylem cambial derivatives. Results: Our research revealed a shift in the composition of xylem components in figured Karelian birch, characterized by increased parenchymatization and reduced vessel quantity. In all studied trunk tissues of Karelian birch, compared with common silver birch, an increase in the expression of the CWINV gene family and the SUS3 gene and a decrease in the expression of SUS4 were shown. Conclusion: Therefore, the increase in parenchymatization in figured Karelian birch is linked to a shift in sucrose metabolism towards the apoplastic pathway, indicated by a higher cell wall invertase activity and gene expression. The expression of the SUS4 gene correlates with the decrease in xylem increments and vessel proportion. The research findings will enhance our understanding of how sucrose breaking enzymes regulate secondary growth in woody plants and aid in developing practical timber cultivation methods.
Keywords: gene expression